Gênero, discurso e poder em três traduções brasileiras de Um bonde chamado desejo - Magalhães, Micaela Rodrigues de Souza Fraga de (2017)
A Streetcar Named Desire, a play written by Tennessee Williams, is considered one of the most important canons in the history of American Theater. His text was broadly played, adapted, translated and is frequently quoted in mainstream audiovisual works. In Brazil, the play - with two original texts in English - was translated by Pedreira (1976), Nikitin (2004), and ViégasFaria (2008). Through an interdisciplinary approach based on Language Studies and on Translation Studies, this research aims to elaborate a comparative analysis on the construction of the character Blanche DuBois in both translations. Focusing on discoursive marks related to the female discourse, it will analyze the ways in which this character diverges from social conventions that she was expected to follow as a woman, and her incessant pursuit to reconfigure herself - from the perspective of each translation. The study will rely on the analytical tools provided by the sociocognitive model of van Dijk (2010, 2012a, 2012b, 2012c), which considers the relation among society, cognition and discourse when creating its analysis categories. An investigation that accounts for the social dimension of language as well as the individual aspects that influence the existing relation between text production and reception, provides us with tools that contribute to explaining the structural differences, therefore the possible ideological differences, to be investigated in the translations of Williams’ work in our country. Finally, it is then concluded that the literary discourse, as the political or advertising ones, can be considered a conducive environment for the analysis of ideologies present in the enunciation of the social actors and actresses who take part in his production. Art, as in translation, is not ideologically neutral, and the image of the woman depicted in novels and plays written by men have a lot to say regarding the construction of stereotypes that hamper the feminine existence.